2014
DOI: 10.3354/esr00554
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of immature green turtle abundance and somatic growth in Puerto Rico

Abstract: Understanding conservation needs relies on robust estimates of key population parameters, such as survival, abundance and somatic growth. We investigated the somatic growth and abundance dynamics of 2 aggregations of immature green turtles, at Tortuga Bay and Puerto Manglar (Culebra, Puerto Rico), throughout 15 yr of capture-mark-recaptures. We used nonlinear models to investigate the effects of carapace length, sampling year, growth interval and the presence of fibropapillomas on growth rates, and used the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 43 publications
(75 reference statements)
4
38
0
1
Order By: Relevance
“…While our study has provided valuable data regarding the movements of juvenile hawksbill turtles around an offshore developmental habitat, other methods of long-term monitoring, such as satellite telemetry and stable isotope analysis, would permit insights even if tracked individuals were to leave the atoll (Shimada et al 2014). Technological advances aside, with suffi-cient commitment of time and resources, there is also much still to be gained from traditional capturemark-recapture methods (Patrício et al 2014). What will ultimately enable a more complete understanding of the niche that hawksbills fill within reef ecosystems is an integrative approach, in which multiple methods, populations, and locations are used to fill the gaps in ecology (Hart & Hyrenbach 2009, Godley et al 2010, Scales et al 2011).…”
Section: Future Directionsmentioning
confidence: 99%
“…While our study has provided valuable data regarding the movements of juvenile hawksbill turtles around an offshore developmental habitat, other methods of long-term monitoring, such as satellite telemetry and stable isotope analysis, would permit insights even if tracked individuals were to leave the atoll (Shimada et al 2014). Technological advances aside, with suffi-cient commitment of time and resources, there is also much still to be gained from traditional capturemark-recapture methods (Patrício et al 2014). What will ultimately enable a more complete understanding of the niche that hawksbills fill within reef ecosystems is an integrative approach, in which multiple methods, populations, and locations are used to fill the gaps in ecology (Hart & Hyrenbach 2009, Godley et al 2010, Scales et al 2011).…”
Section: Future Directionsmentioning
confidence: 99%
“…comm.). At Puerto Manglar, a positive trend on abundance with a mean annual increase of 10.9% was observed over the course of 15 years ( , Patrício et al, 2014, more accentuated from 2006, owing to increased recruitment. This reflects the positive trend in the source populations (Chaloupka et al, 2008), which may lead to changes in the relative contributions from Atlantic rookeries to the Culebra aggregation, particularly if they are not all recover at the same pace.…”
Section: Temporal Variabilitymentioning
confidence: 94%
“…A longterm capture-mark-recapture (CMR) program has revealed that immature turtles remain in these bays for several years (ca. 10 to 17 years, Patrício et al, 2014), and that larger immature turtles (>65 cm SCL) permanently emigrate, potentially to subadult foraging sites closer to their breeding grounds (Patrício et al, 2011). As turtles spend such a long period of their early life at these developmental sites, mortality there can impact the multiple rookeries to which they are linked.…”
Section: Impact For Nesting and Breeding Recruitmentmentioning
confidence: 99%
See 2 more Smart Citations